Factors Measuring Client Satisfaction on Stock Broker Services in Pokhara Valley - Ranabhat, Deepesh; Subedi, Sabina; Ranabhat, Mala (Journal of Nepalese Business Studies, 2022)
Customer satisfaction is very important for the success of the business. This study measured the client satisfaction with broker services in Pokhara valley. Convenience sampling technique is used for selection of sample and 385 respondents who were trading stock in secondary market were taken as sample. Different twelve items were used to measure the clients’ satisfaction. Means score, Exploratory Factor Analysis (EFA), and Confirmatory Factor Analysis (CFA) were used for data analysis. The study found majority of the clients are satisfied with the stock brokers’ services in Pokhara valley. Further, responsiveness and trustworthiness were found as the major factors related to clients' satisfaction with stockbroker services. This study concluded that stockbrokers should be more responsive to the clients and their services should be trustworthy to increase the client's satisfaction.